Recurrent Acute Pancreatitis - Khurana, Vishal; Ganguly, Ishita (JOP. Journal of the Pancreas, 2014)
Recurrent acute pancreatitis (RAP) is commonly encountered, but less commonly understood clinical entity, especially idiopathic RAP, with propensity to lead to repeated attacks and may be chronic pancreatitis if attacks continue to recur. A great number of studies have been published on acute pancreatitis, but few have focused on RAP. Analysing the results of clinical studies focusing specifically on RAP is problematic in view due to lack of standard definitions, randomised clinical trials, standard evaluation protocol used and less post intervention follow-up duration. With the availability of newer investigation modalities less number of etiologies will remains undiagnosed. This review particularly is focused on the present knowledge in understanding of RAP. Image: Recurrent acute pancreatitis: overview and algorithm for evaluation of a case.